EVALUASI KEBERHASILAN PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN PALLEKO KABUPATEN TAKALAR TAHUN 2022 - AP, A.Rizki Amelia; Adinda, Andi Sri; B, Nurul Hikmah (PT.Mantaya Idea Batara, 2022)
The PKH is a conditional non-cash social assistance provided to poor families registered in the Social Welfare Integrated Data.This study aims to obtain more in-depth information regarding the Implementation of the Policy on the PKH. This research is a quasi-qualitative research where the informants are determined by purposive sampling technique as many as 7 informants, namely 1 key informant, 2 regular informants and 4 supporting informants. Data was collected bymeans of in-depth interviews, direct observation and document searches. The resultsshowed that the implementation of the PKH policy had been carried out properly. group formation, verification, and data updating were carried out routinely and on time. This study suggests that local governments improve the quality of the Family Hope Program (PKH), which is expected to strengthen and maximize policies in helping the poor to meet their needs, especially in the health sector.